Recent Advances on Drugs and Vaccines for COVID-19 - Fang Peng MD; Hao Yuan PhD; Sixian Wu MD; Yifeng Zhou MD (SAGE Publishing, 2021)
The current situation of Coronavirus Disease 2019 (COVID-19) worldwide is still very severe. Presently, many breakthroughs have been accomplished in the research and development of drugs for the treatment of COVID-19, especially vaccines; however, some of the so-called COVID-19-specific drugs highlighted in the early stage failed to achieve the expected curative effect. There is no antiviral therapy available, by stimulating protective immunity vaccine is the best choice for the future management of infection. Therefore, we aimed to identify the latest developments in the research and development of these drugs and vaccines and provide a reference for the prevention and treatment of COVID-19.